Evolution of depressive symptoms from before to 24 months after bariatric surgery: A systematic review and meta‐analysis. (23rd February 2023) - Woods, Robbie; Moga, Ana M.; Ribeiro, Paula A. B.; Stojanovic, Jovana; Lavoie, Kim L.; Bacon, Simon L.
Summary: Aims: Depression after bariatric surgery can lead to suboptimal health outcomes. However, it is unclear how depressive symptoms evolve over the 24 months after surgery. We determined the extent depressive symptoms changed up to 24 months after bariatric surgery and how this was impacted by measurement tool and surgical procedure. Methods: We conducted a systematic review and meta‐analysis, searching five databases from database inception to June 2021 for studies that prospectively measured depressive symptoms before and up to 24 months after bariatric surgery. Change scores were converted to Hedge's g, and analyses were performed using mixed‐effects models. Subgroup analyses examined differences across time of follow‐up, measurement tool, and surgical procedure. Findings: Forty‐six studies met inclusion criteria (32, 342 patients). Meta‐analysis indicated a postsurgical reduction in depressive symptom scores that were significant (large effect, g = 0.804; 95% CI: 0.73–0.88, I 2 = 95.7%). Subgroup analyses found that symptom reductions did not differ between the timing of follow‐up periods, measurement tool, and surgical procedure. Conclusions: Depressive symptom scores reduced substantially following surgery; comparable decreases occurred 6 through 24 months after surgery. These findings can help inform practitioners of the typical evolution of depressive symptoms following surgery and where deviations from this may require additional intervention.